Media Sosial sebagai Sarana Pembentukan Karakter Keteladanan Siswa dalam Pembelajaran PAI - Laila Yulianah; Rahmad Shalahuddin Tri Putra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to identify the formulation of exemplary character and find out the forms of application and obstacles to the use of social media in PAI learning as the formation of exemplary character for students. The importance of this research is to find out that social media can be used positively in forming students' exemplary character through the inspiring content they create. This research uses a descriptive qualitative research method carried out at SMP Negeri 1 Candi involving PAI teachers and students in grades 8 & 9. Data collection techniques were obtained through observations, interviews and documentation analysis. The results of this research show that the use of social media not only increases students' creativity in carrying out assignments, but also strengthens their understanding and appreciation of students' exemplary values. One application is conveying inspirational messages, where social media is used to spread Islamic values that can inspire students and other social media users. Social media acts as a means to improve students' creativity, communication skills and critical thinking abilities through creating educational content that is relevant to Islamic values. However, this research also has several challenges such as limited internet access and students' lack of confidence in sharing content. The research conclusion shows that social media has the potential to shape students' exemplary character, with support from the school to overcome existing obstacles.